Distres Psikologis dan Strategi Koping Istri dalam Menghadapi Keterlibatan Suami Judi Online - Risna Rahmawati; Zarina Akbar; Mira Ariyani (IDEA: Jurnal Psikologi, 2026)
The rising phenomenon of online gambling in Indonesia has created significant psychological impacts on wives as part of the family system affected by digital addictive behavior. This study aims to identify the forms of psychological distress and coping strategies used by wives in dealing with their husbands’ involvement in online gambling through a Systematic Literature Review (SLR) approach. Article searches were conducted in Scopus and Google Scholar databases for publications from 2019 to 2025 using the PRISMA 2020 guidelines, resulting in 15 eligible studies analyzed through thematic synthesis. The findings indicate that wives experience multidimensional psychological distress, including financial anxiety, emotional exhaustion, helplessness, secondary trauma, and relational insecurity. The coping strategies identified include problem-focused coping, emotion-focused coping, avoidance coping, and spiritual-religious coping, with their effectiveness strongly influenced by social support, coping flexibility, and the patriarchal cultural context. Furthermore, previous studies show limitations in comprehensively integrating psychosocial aspects within the Indonesian cultural setting. These findings highlight the importance of culturally and gender-sensitive family-based psychological interventions to strengthen the psychological resilience of wives affected by their husbands’ online gambling behavior.